Pengaruh Harga, Kualitas Produk, Citra Merek, dan Promosi Terhadap Keputusan Pembelian dan Pembelian Ulang Smartphone Xiaomi - Sulis Wahyu Putra Pambela; Minto Waluyo (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
The increasingly rapid development of smartphone technology has made smartphone manufacturers compete in creating classy products in order to attract consumers in making purchasing decisions, especially Xiaomi vendors. Xiaomi ranks 5th in market share in Indonesia in 2023, which proves the need for improvements in terms of price, product quality, brand image and promotion. This research aims to determine price, product quality, brand image and promotion. Purchase and repurchase decisions are affected. This research can be used as a strategy to compete with other competitors. This research uses the Structural Equation Modeling method. This research was conducted by distributing questionnaires to 135 Xiaomi smartphone users. The results of this research show that price and brand image have a significant impact on purchasing and repurchasing decisions. Xiaomi is advised to improve the promotional aspect. It is possible that if Xiaomi management makes improvements to the promotional variables, it will be able to win the smartphone market share in Indonesia again.